2022
DOI: 10.3390/mi13122065
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Self-Powered Biomedical Applications Using Triboelectric Nanogenerator

Abstract: The triboelectric nanogenerator (TENG) is a promising research topic for the conversion of mechanical to electrical energy and its application in different fields. Among the various applications, self-powered bio-medical sensing application has become popular. The selection of a wide variety of materials and the simple design of devices has made it attractive for the applications of real-time self-powered healthcare sensing systems. Human activity is the source of mechanical energy which gets converted to elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 117 publications
0
1
0
Order By: Relevance
“…Since the first invention by Wang et al in 2012, sensors that are based on triboelectric nanogenerators (TENGs) have attracted strong attention because they can dynamically monitor the physiological condition of our body and environmental stimuli with high sensitivity at the triboelectric interface while converting environmental mechanical energy into electric energy [ 1 ]. Due to the advantages of high compatibility, customization, and portability, TENG-based self-powered systems have shown great potential in the ever-growing intelligent device market, and their application is rapidly extending to various fields, including artificial intelligence [ 2 ], Internet of things, energy conversion from ocean waves [ 3 ], biomedicine [ 4 ], disability assistance, and so on, where the TENG is either a power source, a self-powered sensor, or in most cases, both [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first invention by Wang et al in 2012, sensors that are based on triboelectric nanogenerators (TENGs) have attracted strong attention because they can dynamically monitor the physiological condition of our body and environmental stimuli with high sensitivity at the triboelectric interface while converting environmental mechanical energy into electric energy [ 1 ]. Due to the advantages of high compatibility, customization, and portability, TENG-based self-powered systems have shown great potential in the ever-growing intelligent device market, and their application is rapidly extending to various fields, including artificial intelligence [ 2 ], Internet of things, energy conversion from ocean waves [ 3 ], biomedicine [ 4 ], disability assistance, and so on, where the TENG is either a power source, a self-powered sensor, or in most cases, both [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that a healthy resting heart rate should range between 50 and 70 beats per minute [21]. Electrocardiography (ECG) electrodes convert beats into voltage, which then produce extremely weak signals ranging from 0.5 mV to 5.0 mV [22].…”
Section: Introductionmentioning
confidence: 99%